1997
DOI: 10.3109/02652049709015329
|View full text |Cite
|
Sign up to set email alerts
|

In vitroCiprofloxacin release from poly(lactide-co-glycolide) microspheres

Abstract: Biodegradable microspheres of PLGA (75:25 and 50:50) containing Ciprofloxacin (CIPRO) were prepared by two different procedures based on: (i) solvent-evaporation, and (ii) evaporation-extraction of the organic phase. The encapsulation rates from the different formulations were quite variable, as well the release patterns of the drug from the microspheres. The evaporation-extraction method seems to be more efficient for the CIPRO encapsulation compared with the solvent evaporation method. The 50:50 PLGA composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…7). This initial rapid release can be attributed to the drug particles localized at the surface, which can rapidly dissolve in the aqueous medium, as previously observed for other hydrophilic drugs encapsulated in nano-and microspheres of PLGA [35,36,38]. It should be noted that ciprofloxacin hydrochloride has a high solubility in water (3.5 g/ 100 ml) and drug crystals rapidly dissolve in the release medium [31]; therefore drug crystals encapsulated in the most external region of PLGA particles can complete the dissolution in few hours.…”
Section: Ciprofloxacin Releasementioning
confidence: 71%
See 2 more Smart Citations
“…7). This initial rapid release can be attributed to the drug particles localized at the surface, which can rapidly dissolve in the aqueous medium, as previously observed for other hydrophilic drugs encapsulated in nano-and microspheres of PLGA [35,36,38]. It should be noted that ciprofloxacin hydrochloride has a high solubility in water (3.5 g/ 100 ml) and drug crystals rapidly dissolve in the release medium [31]; therefore drug crystals encapsulated in the most external region of PLGA particles can complete the dissolution in few hours.…”
Section: Ciprofloxacin Releasementioning
confidence: 71%
“…In the present work, subsequent hardening of the droplets on the superamphiphobic surfaces ensured 100% ciprofloxacin encapsulation yield, as the contact of the drug with the surface is minimum during the particle processing. It should be noticed that the highest loading tested corresponded to 0.2 mg drug mg À1 of microparticle, which is one order of magnitude greater than those previously attained by encapsulating ciprofloxacin in PLGA particles via solvent-evaporation and evaporation-extraction methods [35]. Compared to other active substances and methods to prepare spherical particles, such as the precision particle fabrication (PPF) technology [36], the superamphiphobic-surface-based method is advantageous in terms of total amount of drug encapsulated (nearly 10 times greater), encapsulation efficiency (100% vs. 50-90%), and simplicity in terms of liquid phases used and processing set-up and time.…”
Section: Plga Spherical Particlesmentioning
confidence: 96%
See 1 more Smart Citation
“…HCl-Eudragit RS 100 microspheres were prepared via emulsion solvent evaporation method. Martinez et al (1997) have reported the preparation of poly (DL-lactide-coglycolide,PLGA) ciprofloxacin microspheres. They used both the solvent evaporation method and the evaporation-extraction method to prepare sustained release biodegradable microspheres.…”
Section: -Introductionmentioning
confidence: 99%
“…28 The release of ciprofloxacin from a polymer matrix (implant of screw and microsphere) has been attempted. [29][30][31][32] The ester carbonyl of aliphatic polyester may also help in binding to hard M III -cations, in addition to carbonyl oxygen donors in amides, and ultimately inhibit bacterial proliferation. Drug conjugated nanofibers can also mitigate scarring and pain in patients because of their hydrolytic quality and the subsequent enzymatic degradation of PLA into carbon dioxide and water.…”
Section: Introductionmentioning
confidence: 99%